Gambaran Tingkat Stres Remaja Panti Asuhan di Kota Padang Ditinjau dari Perbedaan Jenis Kelamin - Pebriani, Arini Sri; Susanti, Roza Eva (YASIN, 2024)
Is a critical developmental period characterized by significant physical and psychological changes. Teenagers living in orphanages, in particular, experience stress due to internal and external demands. This study aims to determine the description of stress levels in teenagers living in orphanages in Padang City in terms of gender differences. The type of research used is descriptive quantitative. The sample in this study was random sampling which amount 268 people in 6 different orphanages in Padang city. The instrument used was the DASS 14 questionnaire, with a cross-sectional study research design. The results of the hypothesis test using the Mann-Whitney test indicate a significance value of 0.001. Since the p-value (0.001) is less than 0.05, it can be concluded that there is a significant difference in stress levels between male and female adolescents living in orphanages in Padang City. The study results show that the stress levels of adolescents in the orphanage tend to be low. However, the orphanage management should still anticipate factors that could increase the stress levels of these adolescents.